Pengaruh Model Pembelajaraninquirytraining Berbasis Kolaboratif Terhadap Keterampilan Proses Sains Materi Sumber Daya Alam di SD Methodist 1 Medan - Sari, Dyan Wulan; Kistian, Agus (Unversitas Katolik Santo Thomas, 2020)
This study aimed to analyze. The Influence of learning model on students science process skill. This study is a quasi-experimental research (quasi experiment). The population of this research is fourth grade students of SD Methodist 1 Medan. The sample in this study selected by purposive random sampling as much as two gradtahun es. Class experiment treated with a inquiry training model based collaborative, the control class treated with direct instruction model. The instrument used consisted of: science process skill test and scientific attitude questionnaire sheet. Data analysis was performed using ANOVA two lanes. The results of this study indicate that: (1) the process of science students that learned Science with learning inquiry training model based collaborative is higher than direct instruction; (2) Science process skill students with high scientific attitudes indicates is higher than low scientific attitudes; and (3) an interaction between the inquiry training model based collaborative and direct instruction with the level of scientific attitudes in influencing student science process skills. The results of this research suggest that the learning model inquiry training based collaborative is a solution to and alternatives for the teachers to improve student science process skills.